PRODUCTION PERFORMANCE OF MALE LOCAL DUCKS (ANAS PLATHYRHINCHOS) GIVEN BETEL (PIPER BETLE LINN) LEAVE EXTRACT SOLUTION INCLUDED IN COMMERCIAL RATION - Rohimah, Irma; Dihansih, Elis; Kardaya, Dede (Universitas Djuanda Bogor, 2017)
This study was aimed at assessing production performance of male local ducks(Anasplathyrhinchos) given betel (Piper betle Linn) leave extract solution included in commercial ration. The study was conducted at the Poultry Farm of Departement of Animal Husbandry, Faculty of Agriculture, Djuanda University, Bogor from June to August 2016. Twenty-four male local ducks aged 2 weeks with average body weight of 450 g were used. BR-21E commercial feed of PT SintaFeedmill and betle leaf extract solution were used. A completely randomized design with 4 treatments and 3 replicates was used. Treatments consisted of 100% commercial feed (R0), commercial feed + 2.5% piper betel solution (R1), commercial feed + 5.0% piper betel solution (R2), and commercial feed + 7.5% piper betel solution (R3). Data were subjected to an analysis of variance. Measurements were taken on feed intake, body weight gain, feed conversion rate, and mortality rate. Results showed that treatments did not give any significant effects (P>0.05) on all parameters measured. Key words: production performance, male local duck, betel leaf extract solution.